Three-dimensional MRI study of the relationship between eye dimensions, retinal shape and myopia - Pope, James M. (Biomed Opt Express, 2017)
We investigated changes in eye dimensions and retinal shape with degree of myopia, gender and race. There were 58 young adult emmetropes and myopes (range –1.25D to −8.25D), with 30 East-Asians (21 female/9 male), 23 Caucasians (16/7) and 5 South-Asians (1/4). Three-dimensional magnetic resonance imaging was undertaken with a 3.0 Tesla whole-body clinical MRI system using a 4.0 cm receive-only surface coil positioned over the eye. Automated methods determined eye length, width and height, and curve fitting procedures determined asymmetric and symmetric ellipsoid shapes to 75%, 55% and 35% of the retina. With myopia increase, eye dimensions increased in all directions such that increase in length was considerably greater than increases in width and height. Emmetropic retinas were oblate (steepening away from the vertex) but oblateness decreased with the increase in myopia, so that retinas were approximately spherical at 7 to 8D myopia. Asymmetry of eyes about the best fit visual axis was generally small, with small differences between the vertex radii of curvature and between asphericities in the axial and sagittal planes. Females had smaller eyes than males, with overall dimensions being about 0.5mm less for the former. Race appeared not to have a systematic effect.